P-B13 Comparison of two HPV detection and genotyping systems in a Nigerian screening population. (January 2016) - Modibbo, Fatima; Kasius, Annemieke; Iregbu, Kenneth; Leeman, Annemiek; Oluwande, Oluwatoyosi; De Koning, Maurits; Quint, Wim; Adebamowo, Clement
Abstract : Objectives: To compare the SPF10 system to the GP5+/6+ system for high risk HPV (hrHPV) screening on cervicovaginal samples in Nigeria. Methods: In Karu, a suburban district of Abuja, Nigeria, 400 women were randomized for a self- or hospital-collection after flyer recruitment. A volume of 250 μL was used for DNA isolation with the MagNA Pure and 750 μL was used for nucliSENS easyMAG isolation. MagNA Pure isolates were tested with the SPF10-PCR-DEIA-LiPA25, version 1 system, a test often used in epidemiological studies. GP5+/6+-PCR-EIA, a clinically validated cervical cancer screening method, followed by Luminex genotyping was performed on the nucliSENS easyMAG isolate. qPCR was done (RNaseP) to assess the level of human DNA. Results: Samples of 298 women (74.5% response), with a mean age of 41.1 (SD 7.8, Range 30–62) years were included. The SPF10 showed 23.8% hrHPV+ versus 10.4% with the GP5+/6+. The SPF10 found 9 (3%) samples positive for HPV genotype 16 or 18 versus 4 (1%) by GP5+/6+. Comparing HPV genotypes identified by both systems, 22/29 (75.9%) had concordant genotypes, with the SPF10 system finding additional (low risk) genotypes. Conclusions: Cervical cancer screening by hrHPV testing seems feasible in Nigeria. Corresponding with previous studies (Hesselink et al, 2008), the level of hrHPV+ found by SPF10 was higher compared to GP5+/6+. HrHPV genotyping with both systems showed good agreement. To assess the clinical relevance of any hrHPV+ result, a follow-up study collecting a colposcopy directed biopsy and a repeat hrHPV test is being performed. Results are expected by September 2015.